2017
DOI: 10.3390/ijerph14070775
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Anxiety-Related Postings on Sina Weibo

Abstract: This study examines anxiety-related postings on Sina Weibo to gain insight into social networking about mental health. The themes of a random sample of anxiety-related postings (n = 1000) were assessed. The disclosure of anxiety was the most common theme. The prevalence of anxiety was higher in certain areas where the economy is stronger than others, and the people living there suffered from more stress. Users who talked about feeling anxious tended to be more active on social media during leisure hours and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…It is worth noting that identified users in this study were not clinically diagnosed. Some of them might also be high on neuroticism just like the users identified in an anxiety-related study [ 40 ]. People who score high tend to express more feelings of anxiety or depression than average [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that identified users in this study were not clinically diagnosed. Some of them might also be high on neuroticism just like the users identified in an anxiety-related study [ 40 ]. People who score high tend to express more feelings of anxiety or depression than average [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Golder et al [10] pioneered in using real-time user-generated textual data from Twitter and analyzing the daily changes of positive affect and negative affect, which was the flagship study involving social media data for analyzing emotion-related outcomes. Several following studies have shown the feasibility of using social media data to investigate various health-related issues in the general population, including sleep complaints, depression, anxiety, suicide, and HIV [11][12][13][14]. However, similar studies using social media data are rare for the HIV risk population, men who have sex with men (MSM).…”
Section: Introductionmentioning
confidence: 99%
“…The Lindeman, Merenda, and Gold (LMG) model is used to evaluate the relative importance of each factor, and a geographic detector is applied to calculate the interaction of the influencing factors in step (3). The geographically weighted regression (GWR) model is used for the regression analysis in step (4).…”
Section: B Methods and Modelsmentioning
confidence: 99%
“…When no consensus was reached regarding the label, the majority decision principle was adopted. According to previous studies, the support vector machine (SVM) has high accuracy in Weibo text classification [3], [19]. Thus, the SVM was employed to distinguish the target Weibo texts.…”
Section: Data Collection and Preprocessing 1) Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation